Identifying risk and preventing progression to Type 2 diabetes in vulnerable and disadvantaged adults: a pragmatic review. Issue 1 (13th December 2012) - Taylor, J.; Cottrell, C.; Chatterton, H.; Hill, J.; Hughes, R.; Wohlgemuth, C.; Holt, R. I. G.
Abstract Aim To identify effective approaches to recognize diabetes risk and prevent progression to Type 2 diabetes in vulnerable groups, whose diabetes risk may be difficult to identify or manage. Methods UK‐based interventions that assess diabetes risk and/or target known risk factors were identified through four main sources: submissions to two calls for evidence by the National Institute for Health and Clinical Excellence; local practice examples collected via a targeted email questionnaire; selected electronic databases; and a focused search of relevant websites. No restriction was placed on the study type or evaluation methods used. Key themes and sub‐themes on outcomes, as well as facilitators and barriers to successful delivery, are reported. Results Twenty‐four interventions met all inclusion criteria: 15 included a risk identification element and 14 included preventative activities. A range of risk identification tools were used to improve diagnosis of unmet diabetes‐related health needs and raise awareness of diabetes risk factors. All preventative interventions focused on lifestyle change. No interventions monitored blood glucose as an outcome and only one reported improvements in baseline risk scores. Facilitators included tailored and flexible programme design, outreach delivery in familiar locations and effective inter‐agency working. Barriers included literacy and language difficulties, transient participant populations, low prioritization of diabetes prevention and cost. Conclusions It is possible to engage successfully with high‐risk adults in vulnerable groups to achieve positive health outcomes relevant to the prevention of diabetes. However, more robust evidence on longer‐term outcomes is required to ensure that programmes are targeted and delivered appropriately.